Innovation among entrepreneurial SMEs during the COVID-19 crisis in Iran - Howard E. Van Auken; Mohammad Fotouhi Ardakani; Shawn Carraher; Razieh Khojasteh Avorgani (Small Business International Review)
COVID-19 is affecting the development of the global economy and threatening the survival of SMEs worldwide. In light of the current situation, this paper examines the factors affecting product and process innovation in SMEs during the COVID-19 crisis. We carried out a simple random sample of 185 SME entrepreneurs in Ardakan, Iran, using a multivariate regression analysis. The results showed that experience is one of the most important factors affecting innovation. Organization size and age were negatively associated with process innovation during the current crisis. Moreover, the findings reveal that training to facilitate cooperation as well as higher commitment to R&D can lead to greater innovation. An important conclusion is that, during the COVID-19 pandemic, government efforts to encourage SMEs to create new products helped them to withstand the crisis. The study suggests that, during the COVID-19 crisis, embracing innovation as a core organizational value helped SMEs to remain competitive.